The Oxford Implementation Index: a new tool for incorporating implementation data into systematic reviews and meta-analyses. - Montgomery, Paul; Underhill, Kristen; Gardner, Frances; Operario, Don; Mayo-Wilson, Evan (Journal of clinical epidemiology, 2013)
This article presents a new tool that helps systematic reviewers to extract and compare implementation data across primary trials. Currently, systematic review guidance does not provide guidelines for the identification and extraction of data related to the implementation of the underlying interventions.